Worlds of Labour Turned Upside Down Revolutions and Labour Relations in Global Historical Perspective - Brandon, Pepijn; Jafari, Peyman; Müller, Stefan (Studies in Global Social History, 2021)
This volume offers a bold restatement of the importance of social history for understanding modern revolutions. The essays collected in Worlds of Labour Turned Upside Down provide global case studies examining: - changes in labour relations as a causal factor in revolutions; - challenges to existing labour relations as a motivating factor during revolutions; - the long-term impact of revolutions on the evolution of labour relations. The volume examines a wide range of revolutions in the nineteenth and twentieth centuries, covering examples from South-America, Africa, Asia, and Western and Eastern Europe. The volume goes beyond merely examining the place of industrial workers, paying attention to the position of slaves, women working on the front line of civil war, colonial forced labourers, and white collar workers.